Microbial consortium formulation in liquid organic fertilizer for managing bacterial leaf blight (Xanthomonas oryzae pv. oryzae), rice blast (Pyricularia oryzae), and enhancing rice productivity - SUHARTININGSIH DWI NURCAHYANTI; RACHMI MASNILAH; SUBHAN ARIF BUDIMAN; AHMAD ILHAM TANZIL; ANGGI ANWAR HENDRA NURDIKA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nurcahyanti SD, Masnilah R, Budiman SA, Tanzil AI, Nurdika AAH. 2024. Microbial consortium formulation in liquid organic fertilizer for managing bacterial leaf blight (Xanthomonas oryzae pv. oryzae), rice blast (Pyricularia oryzae), and enhancing rice productivity. Biodiversitas 25: 2208-2220. The productivity of rice is significantly influenced by soil fertility and plant diseases as limiting factors. The overreliance on synthetic fertilizers and pesticides in rice cultivation has led to declining land quality. We propose the utilization of Liquid Organic Fertilizers (LOF) enriched with beneficial microbes as a sustainable solution to maintain soil fertility and protect plants from pathogens. Our research specifically focuses on the formulation of LOF enriched with the microbial consortium to enhance rice productivity and suppress bacterial leaf blight (Xanthomonas oryzae pv. oryzae), and rice blast (Pyricularia oryzae) diseases. The three LOF treatments were formulated from vegetable and fruit waste (FV), Rice Straw (RS), and Cattle Manure (CM) with a microbial consortium consisting of Pseudomonas putida Pf10, Bacillus subtilis JB12, and Trichoderma sp. The results showed that the LOF from the three materials is suitable for the growth of the microbial consortium with a population of 104-109 CFU/mL, has macro-micronutrient content, pH at 6.5-6.8, and C-organic to support plant growth. The applications of the three types of LOF were able to suppress the severity of bacterial leaf blight by up to 21% and rice blast by 4% at eight weeks after inoculation. All LOF treatments are capable of enhancing the growth and production of rice. There were no significant differences in LOF materials for disease suppression, growth, and rice production.